Testosterone replacement relieves ligature-induced periodontitis by mitigating inflammation, increasing pro-resolving markers and promoting angiogenesis in rats: A preclinical study - Pelegrin, Álvaro Formoso [UNESP]; de Paiva Gonçalves, Vinícius; Carvalho, Jhonatan de Souza [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Spolidorio, Luís Carlos [UNESP] (Elsevier, 2023)
Objectives: This study aimed to evaluate the inflammatory profile as well as the resolution of inflammation in a ligature-induced periodontal inflammation in rats with depletion and/or supraphysiological testosterone replacement. Design: Sixty male rats (Holtzman) were used in the present study. Study groups were created as following: (1) Sham (no testicle removal); (2) Orchiectomy (OCX), 3) OCX + Testosterone (OCX + T); (4) Sham + Ligature (SH + L); (5) OCX+L; and 6) OCX + T + L. The surgeries were performed on day 1, and testosterone was administered weekly since day 1. On day 15, a cotton ligature was placed around the lower first molars and maintained for 15 days. Morphological changes in periodontal tissues were determined by histopathological analysis. Immunohistochemistry (factor VIII) and immunoenzymatic assay were performed to evaluate angiogenesis process and (pro- and anti-) inflammatory markers, respectively. Results: Ligature promoted a marked inflammatory gingival infiltrate and bone loss (P < 0.05). Supraphysiological testosterone treatment increased the percentage of blood vessels, extracellular matrix and fibroblasts in the presence and absence of periodontal inflammation (P < 0.05). A high dose of testosterone increased factor VIII+ blood vessels and IL-10 expression in inflamed gingival tissue, while PGE2, LXA4 and MPO were reduced as a result of supraphysiological testosterone administration (P < 0.05). Conclusions: These results, in our experimental model, suggest that supraphysiological testosterone treatment stimulated gingival tissue repair during ligature-induced periodontitis, and it seems to be related to an anti-inflammatory and pro-resolutive mechanism resulting by the modulatory effect on PGE2 and IL-10 related to an enhanced angiogenesis.
Keywords: Hormone replacement therapy; Inflammation; Periodontal diseases; Testosterone